Utilizing NACA Ducts and an Inner Turbine System in a High-Power Rocket to Generate an Electric Current - Lenz, Kathryn Elizabeth; Juckem, David Anthony (Proceedings of the Wisconsin Space Conference, 2018)
During the 2016-2017 Collegiate Rocket Launch (CRL) competition, teams were required to design and construct a high-power rocket that would complete a safe flight that would reach as close as possible to a target apogee height of 3,000 feet, as well as generate an electric current during the pre-apogee portion of the rocketâ€™s flight. The UW-Fox Valley team, the Rocketeers, designed a three-inch diameter, thin-walled fiberglass airframe at a final length of 188cm that was able to achieve safe flights. In order to generate electricity during the flight, the team used a ducting system that allowed air through an inner turbine system. On competition day, three safe flights were completed, with altitude, velocity, and acceleration data recorded. Electric generation data was recorded during the first flight, but due to environmental factors data was not recorded for voltage generation on the second and third flight. Â 